An experimental Nash program: A comparison of non-cooperative v.s. cooperative bargaining experiments - Michela Chessa; Nobuyuki Hanaki; Aymeric Lardon; Takashi Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2023)
This paper aims to contribute to the literature on Nash program by experimentally comparing the results of "structured" (non-cooperative) demand-based and offer-based mechanisms that implement the Shapley value as an ex-ante equilibrium outcome with the results of corresponding "semi-structured" (cooperative) bargaining procedures. A significantly higher frequency of the grand coalition formation, the higher efficiency, and the allocation belonging to the bargaining set is observed in the latter than in the former regardless of whether it is demand-based or an offer-based. While significant differences in the resulting allocations are observed between the two non-cooperative mechanisms, little difference is observed between the two cooperative procedures.
Keywords: C70; C71; C92; 330; Nash Program; Bargaining procedures; Shapley value